Morbidity of Adult Spinal Deformity Surgery in Elderly Has Declined Over Time. Issue 16 (15th August 2017) - Passias, Peter G.; Poorman, Gregory W.; Jalai, Cyrus M.; Neuman, Brian; de la Garza-Ramos, Rafael; Miller, Emily; Jain, Amit; Sciubba, Daniel; McClelland, Shearwood; Day, Louis; Ramchandran, Subaraman; Vira, Shaleen; et al.
Abstract : Study Design: A retrospective review of a prospectively collected database, the Nationwide Inpatient Sample (NIS), years 2003 to 2012. Objectives: The aim of this study was to examine trends in the management of scoliosis in elderly (age >75 yrs) patients from 2003 to 2012. Summary of Background Data: Scoliosis incidence rises with increasing age, and age has been shown to be an independent risk factor for surgical complications in scoliosis surgery. Previous studies have displayed increasing surgical frequency on elderly scoliotic patients in the last decade, but have not investigated complications in the same years. Methods: ICD-9 coding identified elderly (age ≥75 yrs) patients with a primary diagnosis of scoliosis undergoing lumbar fusion or decompression. Analysis of variance (ANOVA) comparisons and linear trend analysis described changes from 2003 to 2012 in surgical invasiveness (Mirza scale: levels fused/decompressed/instrumented and by approach), intraoperative complications, and Charlson Comorbidity Index (CCI). Secondary outcome measures included cost and discharge outcomes. Results: Eight thousand one elderly patients with ASD from 2003 to 2012 were included for analysis. Fusion incidence increased on average 13.8% per year ( P  < 0.001), surgical invasiveness by Mirza scale increased from 2.0 in 2003 to 5.9 in 2012 ( P  < 0.001), and CCI increased from 0.77 to 1.44 (p < 0.001). Over the same interval, elderly patients undergoing fusion displayed overall reduction in complications (excluding anemia)—from 26.7% to 8.6% ( P  < 0.001); specifically, surgical complications decreased from 11.7% to 0.7% ( P  < 0.001) and respiratory complications decreased from 6.7% to 1.4% ( P  = 0.004). Conclusion: From 2003 to 2012, surgical management of ASD in the elderly population increased in incidence and complexity, while number of patient comorbidities increased and in-hospital morbidity decreased. This may indicate increased willingness of surgeon's to operate on elderly patients, and reflect a development of overall understanding of deformity in the past decade. Level of Evidence: 3 Abstract : Supplemental Digital Content is available in the text